2016
DOI: 10.1371/journal.pone.0152228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Practice and Imagery Practice on Bilateral Transfer in Learning a Sequential Tapping Task

Abstract: Recent research on bilateral transfer suggests that imagery training can facilitate the transfer of motor skill from a trained limb to that of an untrained limb above and beyond that of physical practice. To further explore this effect, the present study examined the influence of practice duration and task difficulty on the extent to which imagery training and physical training influences bilateral transfer of a sequential key pressing task. In experiment 1, participants trained on the key pressing task using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 25 publications
(64 reference statements)
7
47
1
1
Order By: Relevance
“…The direction of transfer, however, varies across studies, in that some studies have shown greater transfer after initial practice with the dominant hand [13, 32], while others have shown greater transfer after initial practice with the nondominant hand [15, 17, 33]. The precise reason for this asymmetric transfer is currently not clear, although scientists have linked this observation to the idea of hemispheric specialization for certain movement variables (e.g., kinematic vs. dynamic) [16, 18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The direction of transfer, however, varies across studies, in that some studies have shown greater transfer after initial practice with the dominant hand [13, 32], while others have shown greater transfer after initial practice with the nondominant hand [15, 17, 33]. The precise reason for this asymmetric transfer is currently not clear, although scientists have linked this observation to the idea of hemispheric specialization for certain movement variables (e.g., kinematic vs. dynamic) [16, 18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…encoding results relative to physical practice 6 . In contrast, a bout of physical practice-based training leads to inferior performance with the untrained relative to the trained effector 4 and greater encoding of effector dependent information 6 . In these studies, overall improvements in performance resulting from motor imagery remained inferior to those driven through physical practice 4,6 .…”
mentioning
confidence: 95%
“…El entrenamiento bilateral, conocido como transferencia bimanual, es un proceso donde el sistema neuromotor recupera información relevante para el aprendizaje de la extremidad entrenada y la transfiere a la extremidad opuesta no entrenada. 37 Mediante este fenómeno la experiencia obtenida en un miembro entrenado tiene un impacto beneficioso sobre el miembro contralateral no entrenado. 37,38 Este es un enfoque de gran relevancia para la rehabilitación del ACV, ya que el paciente puede analizar las características de habilidad entrenada y utilizar esa experiencia para favorecer la práctica con el lado afectado.…”
Section: Entrenamiento Bilateralunclassified